4y-9+y+46=8y+40-6y

Simple and best practice solution for 4y-9+y+46=8y+40-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-9+y+46=8y+40-6y equation:


Simplifying
4y + -9 + y + 46 = 8y + 40 + -6y

Reorder the terms:
-9 + 46 + 4y + y = 8y + 40 + -6y

Combine like terms: -9 + 46 = 37
37 + 4y + y = 8y + 40 + -6y

Combine like terms: 4y + y = 5y
37 + 5y = 8y + 40 + -6y

Reorder the terms:
37 + 5y = 40 + 8y + -6y

Combine like terms: 8y + -6y = 2y
37 + 5y = 40 + 2y

Solving
37 + 5y = 40 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
37 + 5y + -2y = 40 + 2y + -2y

Combine like terms: 5y + -2y = 3y
37 + 3y = 40 + 2y + -2y

Combine like terms: 2y + -2y = 0
37 + 3y = 40 + 0
37 + 3y = 40

Add '-37' to each side of the equation.
37 + -37 + 3y = 40 + -37

Combine like terms: 37 + -37 = 0
0 + 3y = 40 + -37
3y = 40 + -37

Combine like terms: 40 + -37 = 3
3y = 3

Divide each side by '3'.
y = 1

Simplifying
y = 1

See similar equations:

| 5(2x-4)=4(2x+1) | | 8+0.09x=14 | | 14-2.2x=-8 | | -16+7k=k-2k | | 6x+3+2x=5x-4 | | -16k+7k=k-2k | | 7.2x-4.9=60.1 | | (32x^2-8x+4)=0 | | 3/7-3x | | (x+5)(x+2)=25 | | 5x^2+2Y^2+2xy-2x-4y+2=0 | | 4x+5+2x+12=180 | | 2x^2+5y^2=16 | | a^2+b^2=625 | | 7(z+3)-3z=44 | | 10+15y=3y | | Sin(3x)+sin(9x)= | | 9-y=15-5y | | 7-y=3-3y | | Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 | | x*ln((8*x^3))+ln((8*x^2))=20-ln(2) | | 72=-16x^2+64x+12 | | 1x=8y+48 | | 2x/2-3x | | 0=-16x^2+64x+8 | | 2(f-3)=f+5 | | 100=60a+[40(2a)] | | -9=x(-10/x) | | 18x+6x-4x+2=2x-10x+16 | | 5x+5=4y-23 |

Equations solver categories